The Impact of PT. Jhonlin's Sugar Cane Plantation on the Welfare of Rice Farmers in Watu-Watu Village, Lantari Jaya District, Bombana Regency - Rigal; Limi, Muhammad Aswar; Slamet, Agustono (International journal of technology and education research, 2025)
The objectives of this study are 1) To analyze the contribution to the income of rice farmers with the existence of PT. Jhonlin Batu Mandiri's sugarcane plantations in Watu-Watu Village, 2) To analyze the welfare of rice farmers on the establishment of PT. Jhonlin Batu Mandiri's sugarcane plantations in Watu-Watu Village, using the Simple Random Sampling Method. The data analysis used was household income analysis, quantitative descriptive analysis to explain the impact of sugarcane plantations on household income of rice farmers, and welfare analysis of rice farmers on the establishment of sugarcane plantations PT. Jhonlin Batu Mandiri in Watu-Watu Village. The results showed: 1) The average expenditure of rice farmers from 42 respondents in one harvest is the highest cost incurred by farmers in Watu-Watu Village, Lantari Jaya District, Bombana Regency, which is fertilizer cost, amounting to Rp. 68,601,000/ha/MT. Meanwhile, the lowest cost is the tax fee, which is Rp. 9,280,000/ha. The average net income or profit of paddy rice farming in Watu-Watu Village, Lantari Jaya District, Bombana Regency was obtained at Rp. 1,237,062,500/ha/MT2) and sugarcane plantations had a positive impact on the household income of rice farmers in Watu-Watu Village, Lantari Jaya District, Bombana Regency. 2) Household welfare: The welfare level of rice farmers in Watu-Watu Village, Lantari Jaya District, Bombana Regency is quite high, with 42 rice farmers surveyed, namely 36 rice farmers who are included in the prosperous category and 6 rice farmers who are included in the unprosperous category, namely farmers in Watu-Watu Village, Lantari Jaya District, Bombana Regency